Exploring the Validity of International Geographical Indications for Indonesian Products: Menjajaki Keabsahan Indikasi Geografis Internasional untuk Produk Indonesia. - Aviva, Srivit; Mediawati, Noor Fatimah (Indonesian Journal of Law and Economics Review, 2024)
Abstract: The increasing globalization of markets has raised significant legal questions regarding the registration of geographical indications (GIs), particularly concerning the validity of registering names from regions outside Indonesia. This research adopts a normative research method utilizing a statute approach to explore the legal framework governing GIs in Indonesia and compare it with international standards. The knowledge gap identified in this study pertains to the lack of comprehensive understanding regarding the requirements for registering foreign geographical names as GIs in Indonesia. The aim of this research is to provide an in-depth analysis of the legal validity of such registrations, focusing on the specific requirements and implications under Indonesian law. Preliminary findings indicate that while foreign regional names can be registered as trademarks if they meet specific criteria, they cannot be registered as GIs due to the absence of unique characteristics attributable to the geographical factors of the foreign country. This study's novelty lies in its comparative perspective, highlighting the discrepancies between local and international GI regulations, thereby enriching the discourse on intellectual property rights in a global context. The implications of this research are significant for policymakers and legal practitioners, as it underscores the necessity for clearer regulations and standards governing the use of foreign geographical names, ultimately aiming to protect consumers and uphold the integrity of Indonesian GIs. Highlights: oreign names may qualify for trademark registration under specific conditions. Geographical indications require unique regional characteristics for registration. Comparative analysis enhances understanding of international geographical indication laws. Keywords: Geographical Indications, Trademark Registration, International Law, Indonesia, Legal Framework